2007
DOI: 10.1002/j.2055-2335.2007.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial Point‐Prevalence Studies to Investigate Hospital Antimicrobial Prescribing

Abstract: Aim: To investigate antimicrobial prescribing patterns using a validated point-prevalence approach and to identify intervention targets to optimise antimicrobial use. Method: 3 prospective point-prevalence studies were conducted over 4-day periods in April 2005, September 2005 and April 2006 at a tertiary hospital using a previously published method. Clinical pharmacists used a standardised data collection form on an allocated day to record details of all patients who were prescribed systemic antimicrobials (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Around 30 to 40% of hospitalised patients are prescribed antimicrobials. 1,2 Studies have demonstrated that up to 50% of antimicrobial use in overseas hospitals is inappropriate, with similar rates of inappropriate antimicrobial use reported in Australian hospitals. [3][4][5][6][7] Therefore, a need to optimise antimicrobial use is clearly evident, especially when there is limited development of new antimicrobials.…”
Section: Introductionmentioning
confidence: 92%
“…Around 30 to 40% of hospitalised patients are prescribed antimicrobials. 1,2 Studies have demonstrated that up to 50% of antimicrobial use in overseas hospitals is inappropriate, with similar rates of inappropriate antimicrobial use reported in Australian hospitals. [3][4][5][6][7] Therefore, a need to optimise antimicrobial use is clearly evident, especially when there is limited development of new antimicrobials.…”
Section: Introductionmentioning
confidence: 92%
“…The main reason for resistance is excessive and irrational antimicrobial use at hospitals and at the community level. ( Smith and Coast, 2002 , Dean et al, 2002 , Ho and Melvani, 2007 , Storr et al, 2017 , O’Neill, J., 2014 ). Inappropriate use of antibiotics is also common in settings in the KSA and strengthens this concern at the global level ( Belkina et al, 2014 , Al-Ghamdi et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…This makes it one of the world's most urgent public health problems. 2 Antimicrobial resistance threatens the very core of modern medicine and the sustainability of an effective, global public health response to the enduring threat from infectious diseases. Without harmonized and immediate action on a global scale, the world is heading towards a post-antibiotic era in which common infections could once again kill.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for resistance is unnecessary and irrational antimicrobial use at hospitals and at the community level. 1,2 To address the increasing burden of multidrug resistant infections antibiotic stewardship programs are promoted worldwide to rationalize prescription of antibiotics and preserve remaining antibiotics.…”
Section: Introductionmentioning
confidence: 99%